Nanocellulose-Based Adsorbent for Cu(II) Adsorption - Ibrahim, Haziqatulhanis; Sazali, Norazlianie; Kadirgama, Kumaran; Wan Salleh, Wan Norharyati; Gunawan, Triyanda; Widiastuti, Nurul; Junaidi, Afdhal (Engineering, Technology & Applied Science Research, 2024)
This study addresses the critical issue of copper removal from wastewater due to environmental and health concerns. Choosing pandan leaves as a source of cellulose was a deliberate decision due to their abundant availability in nature and minimal ecological footprint. Through the utilization of these properties, this study synthesized nanocellulose with enhanced adsorption capabilities by employing chemical pretreatments, sulfuric acid hydrolysis, and acrylamide grafting with the aid of ceric ammonium nitrate (CAN) as an initiator. In order to thoroughly evaluate the synthesized material, X-Ray diffractometer (XRD) and Fourier transform infrared (FTIR) spectroscopy were used. These characterization methods revealed insights into the morphology, functionality, and crystallinity of nanocellulose. The removal of copper(II) ions is investigated by employing an atomic absorption spectrometer (AAS), focusing on three important factors: pH variation, initial concentration, and adsorbent dosage, which are carefully examined. Grafted nanocellulose demonstrates superior performance, achieving over 85% grafting efficiency. Optimal Cu(II) removal conditions are identified at pH 6, with an initial metal ion concentration of 30 ppm and an adsorbent dose of 2.2 g/L. This study not only addresses a critical concern in wastewater treatment, but also explores the potential of pandan leaf-derived nanocellulose as a sustainable solution for heavy metal removal.